Nuclear Size is Regulated by Importin α and Ntf2 in Xenopus - Levy, Daniel L. (2010)
The size of the nucleus varies among different cell types, species, and disease states, but mechanisms of nuclear size regulation are poorly understood. We investigated nuclear scaling in the pseudotetraploid frog Xenopus laevis and its smaller diploid relative Xenopus tropicalis, which contains smaller cells and nuclei. Nuclear scaling was recapitulated in vitro using egg extracts, demonstrating that titratable cytoplasmic factors determine nuclear size to a greater extent than DNA content. Nuclear import rates correlated with nuclear size, and varying the concentrations of two transport factors, importin α and Ntf2, was sufficient to account for nuclear scaling between the two species. Both factors modulated lamin B3 import, with importin α increasing overall import rates and Ntf2 reducing import based on cargo size. Importin α also contributes to nuclear size changes during early X. laevis development. Thus, nuclear transport mechanisms are physiological regulators of both interspecies and developmental nuclear scaling.